Reclassification of Bifidobacterium stercoris Kim et al. 2010 as a later heterotypic synonym of Bifidobacterium adolescentis - Killer, J; Sedláček, I; Rada, V; Havlík, J; Kopečný, J (International journal of systematic and evolutionary microbiology, 2013)
The taxonomic position of Bifidobacterium stercoris Eg1(T) ( = JCM 15918(T)) based on comparative 16S rRNA gene and hsp60 sequence analyses was found to be controversial, as the strain showed high similarity to the type strain of Bifidobacterium adolescentis, CCUG 18363(T). Therefore, the relationship between the two species was investigated by a taxonomic study that included, in addition to re-evaluation of the 16S rRNA gene sequence, determination of DNA-DNA binding and multilocus sequence analysis (MLSA) of housekeeping genes encoding the DNA-directed RNA polymerase B subunit (rpoC), putative xylulose-5-phosphate/fructose-6-phosphate phosphoketolase (xfp), elongation factor EF-G (fusA), 50S ribosomal protein L2 (rplB) and DNA gyrase B subunit (gyrB). Comparative 16S rRNA gene sequence analysis showed relatively high similarity (98.9 %) between B. stercoris KCTC 5756(T) and B. adolescentis ATCC 15703(T). MLSA revealed close relatedness between B. stercoris KCTC 5756(T) and B. adolescentis CCUG 18363(T), with 99.3-100 % similarity between the rpoC, xfp, fusA, rplB and gyrB gene sequences. In addition, relatively high dnaJ1 gene sequence similarity of 97.7 % was found between the strains. Similar phenotypes and a high DNA-DNA binding value (78.9 %) confirmed that B. stercoris and B. adolescentis are synonymous. Based on these results, it is proposed that the species Bifidobacterium stercoris Kim et al. 2010 should be reclassified as a later heterotypic synonym of Bifidobacterium adolescentis Reuter 1963 (Approved Lists 1980).
Keywords: RNA ribozomální 16S; Bacterial Typing Techniques; Ribosomal Proteins; fenotyp; ribozomální proteiny; DNA bakterií; DNA gyráza; Phenotype; multilokusová sekvenční typizace; Bifidobacterium; RNA, Ribosomal, 16S; techniky typizace bakterií; Nucleic Acid Hybridization; fylogeneze; DNA, Bacterial; Aldehyde-Lyases; Sequence Analysis, DNA; elongační faktor G; DNA Gyrase; sekvenční analýza DNA; DNA řízené RNA-polymerasy; DNA-Directed RNA Polymerases; hybridizace nukleových kyselin; molekulární sekvence - údaje; Multilocus Sequence Typing; Molecular Sequence Data; Peptide Elongation Factor G; Phylogeny; aldehydlyasy